2023
DOI: 10.3389/fpsyg.2023.1111195
|View full text |Cite
|
Sign up to set email alerts
|

Mixed comparison of interventions for different exercise types on students with Internet addiction: a network meta-analysis

Abstract: BackgroundInternet addiction (IA) has a significant negative impact on students. The condition of students with IA can be improved by exercise, which has been identified as an effective intervention strategy. However, the relative effectiveness of different exercise types and the most effective ones remains unknown. This study presents a network meta-analysis to compare six exercise types (team sport, double sport, single sport, team + double sport, team + single sport, and team + double + single sport) based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Research has found that compared to non-internet addicted college students, internet addicted college students have higher levels of depression and lower levels of physical activity 52 . Physical activity can mitigate internet addiction by modulating the neurobiology of the central and autonomic nervous systems 53 , thereby significantly reducing depression levels among internet-addicted college students 54 , and this evidence is also supported by retrospective studies 55 . Therefore, we make the final hypothesis of this study that physical activity can regulate the relationship between internet addiction and depression in college students.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Research has found that compared to non-internet addicted college students, internet addicted college students have higher levels of depression and lower levels of physical activity 52 . Physical activity can mitigate internet addiction by modulating the neurobiology of the central and autonomic nervous systems 53 , thereby significantly reducing depression levels among internet-addicted college students 54 , and this evidence is also supported by retrospective studies 55 . Therefore, we make the final hypothesis of this study that physical activity can regulate the relationship between internet addiction and depression in college students.…”
Section: Introductionmentioning
confidence: 79%
“…Additionally, long-term physical exercise can significantly reduce the level of internet addiction and depression among college students, improve sleep quality, and balance the sympathetic and parasympathetic nervous system functions 54 . Moreover, group sports activities are enjoyable and involve social interactions, which may further weaken the depressive emotions caused by internet addiction among college students 55 . Therefore, physical activity can regulate the relationship between internet addiction and depression among college students, confirming our last hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they tend to use the internet for social interaction instead of face-to-face contact, resulting in PIU. On the other hand, a review of studies has shown that different types of exercise (such as single sport, team sport, double sport, and team + double sport) could alleviate internet addiction by improving the mental health of students with internet addiction (such as loneliness and anxiety) [ 72 ]. Meanwhile, Cheng et al [ 39 ] also found that participation in physical exercise was related to the improvement and adjustment of college student’s mental health, and exercise could effectively promote the release of psychological pressure, increase social opportunities, and reduce negative emotions such as loneliness in the process of exercise, thus playing a role in relieving mobile phone addiction.…”
Section: Discussionmentioning
confidence: 99%